THE ANALYSIS OF QUALITY OF TILAPIA (Oreochromis niloticus) POWDER BROTH WITH GINGER (Zingiber officinale) ADDITION - Nurul Afdillah Yusyaf; Anni Faridah; Asmar Yulastri; Sari Mustika (Ikatan Dosen Menulis, 2024)
Tilapia can be used as a flavoring substitute for MSG, but tilapia is included in the category of perisable food (perishable) and smells fishy. So it is necessary to add ginger as a natural preservative because ginger is antimicrobial and reduces the fishy smell in tilapia. The purpose of this research is to analyze the quality of tilapia powder broth with the addition of ginger. This research uses the Pure Experiment Method (True experiment). The treatment studied includes the effect of adding ginger (0%(X0), 2,5% (X1), 5% (X2), 7,5% (X3), and 10%(X4)) on the sensory quality of tilapia powder broth which includes aspects of shape, color, texture, aroma, and taste. Primary data is statistically analyzed using variance analysis (ANAVA) and continued with Duncan Test if Fhitung ≥ Ftable. While secondary data is obtained from relevant literature. The results of the study stated that there is no significant influence on the quality of shape, color, texture, and taste (Fhitung ≤ Ftable) but has a significant effect on the quality of aroma (Fhitung ≥ Ftable). The best value of the aroma quality of tilapia powder broth in X3 and X4 treatment with an average value of 4,53% and 4.85% with less fishy aroma quality.